Peran Teknologi pada Manajemen Purchasing dalam Menarik Konsumen terhadap Produk Minuman Le Mineral PT Tirta Fresindo Jaya - Ahyar Maulana; Deden Nuralif; Nurul Akmal; Muhammad Ponco Wahyuanto (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2025)
To draw in and keep customers in this cutthroat age, businesses must always seek out new and creative ways to enhance promotions. Le Minerale's use of innovative information technology in their advertising is one intriguing example. A qualitative approach method of literature study type was employed in this investigation. Every business must therefore have an effective marketing plan for the goods it manufactures in order to win the competition. so that if sales of a product are high, corporate profits can be made. In this instance, the Le Minerale corporation influences consumer attraction using technologically enabled promotional medium. In the current digital age, technology-based promotional tactics have grown in importance as a means of assisting purchase management in order to draw in customers.